Analisis Terapi Bekam Sebagai Intervensi Masalah Keperawatan Nyeri Akut Pada Keluarga Dengan Tahap Perkembangan Lansia - Arita Murwani; Siti Nur Hidayah; Viantika Kusumasari; Anna Nur Hikmawati (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: One of the problems that often occurs in families with the developmental stage of the elderly is degenerative diseases such as hypertension. Headache and heaviness in the neck are one of the symptoms of hypertension that make it uncomfortable and one of the non-pharmacological therapies to reduce pain is cupping. Aims: To analyze cupping therapy as an intervention for acute pain nursing problems in families with the developmental stage of the elderly. The research method used is a descriptive method with a case study approach. Results: This study indicates that the problem of acute pain is well resolved where there is a decrease in pain levels after cupping therapy is given. Before being given cupping therapy the pain scale was 4 (moderate) and after cupping therapy the pain scale was 1 (mild). Conclusion: This study is that cupping therapy can reduce the scale of acute pain in the elderly through activated skin receptors, causing an increase in blood circulation and blood supply to the skin and internal organs through nerve connections.